2014
DOI: 10.1111/ajco.12259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oncotype DX testing on adjuvant treatment decisions in patients with early breast cancer: A single-center study in the United Arab Emirates

Abstract: This first decision impact study in a Middle Eastern country showed the significant effect of Oncotype DX testing on clinical practice, further demonstrating the consistent impact of such testing worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
5
7
0
Order By: Relevance
“…Similar rates were reported in studies from different parts of the world such as Mexico (45%), Hong Kong (50.7%), United Arab Emirates (53.2%), Turkey (57%), and the United States (59%) [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar rates were reported in studies from different parts of the world such as Mexico (45%), Hong Kong (50.7%), United Arab Emirates (53.2%), Turkey (57%), and the United States (59%) [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 84%
“…More recently, the value of ODX assay was investigated prospectively in the TAILOR-X trial. Patients with midrange RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were randomly assigned to receive either chemo-endocrine therapy or endocrine therapy alone. Results showed that ACT did not improve the outcome of these patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment change was 32% in a pooled meta-analysis of the previous European studies. In Ontario, Canada, the percentage was 38% [12]; Mexico, 32% [13]; Japan, 38% [14]; Hong Kong, 23.3% [15]; and United Arab Emirates, 27.7% [16].…”
Section: Discussionmentioning
confidence: 98%
“…Another example for biological features influencing decision making in oncology is Onco-Type DX assay. Jaafar et al [51] reported that the use of the assay was associated with a significant change in treatment decisions and an overall reduction of chemotherapy use. Also, the Ki-67 Index, although there is no objectively established cutoff point [52][53][54], has predictive and prognostic value and is a utilized marker in clinical practice, for example, it independently improves the prediction of treatment response and prognosis in a group of breast cancer patients receiving neoadjuvant treatment [55].…”
Section: Decision-specific Characteristicsmentioning
confidence: 99%